The struggling farmer: the literary function of some allusions to the Georgics in the Aeneid - Burbidge, J (2007)
In this article I identify a major function of allusion to the Georgics in Vergil's later poem the Aeneid. I argue that pity for various characters or groups in the epic is evoked by associating them with the figure of the struggling farmer from the earlier text. Some of the allusions which I claim have this function have long been recognized by scholars; others that I consider seem not to have been noticed before. In §1, I discuss the Trojans' association with the farmer of the Georgics at various points in Aeneid 2 and 3. In §2 and §3, I look at some passages from later in the epic where the struggles of the farmer are again recalled: by this stage, it tends to be the Italians rather than the Trojans who are aligned with the farmer.